Do texto literário ao filme: dialógos intersemióticos em a hora da estrela. - Silva, ângela Maria Lessa da (2006)
The purpose of this paper is to carry out an analysis of the novel A Hora da Estrela (1977) and the film A Hora da Estrela (1986), based on the perspectives of the Semiotics and the Intersemiotics Translation. Theory the study shows that it is possible to involve distinct languagens in the process of different kinds of Things. Starting from a study of the translating and its conceptions, we discuss the adaptation process of the novel for the seventh art, so as to interweave of the different languages. The analysis is founded on the idea that adaptations can not be considered as faithful or unfaithful, in fact, they are recreations, transpositions, or transcreations in the words of Haroldo de Campos. The theoretical perspective of the study is based on the work of authors such as Júlio Plaza, Eisenstein, Gorlée, Benedito Nunes, in order to provide a richer support to the theoretical and critical analysis of both of literary text and the film, focusing on the intersemiotic dialogues in A Hora da Estrela. They were examined in the light of the literary text as a re-reading of Suzana Amaral whose work establishes a dialogue with as well as interpenetrates the work of Clarice Lispector (1977), offering an updated approach to the construction of the cinematographic narrative.